Development and Initial Psychometric Testing of the Midwifery Practice Climate Scale ‐ Part 2. (7th September 2020) - Thumm, E. Brie; Shaffer, Jonathan; Meek, Paula
Abstract : Introduction: A supportive practice climate is demonstrated to improve patient outcomes, health care provider well‐being, and workforce stability. Midwives are an integral component to improving maternal health care; however, there has been limited research into the qualities and measurement of a supportive practice climate for midwives. Methods: The Midwifery Practice Climate Scale is a self‐report instrument designed to measure midwives' perceptions of their work environments. We tested the scale's validity and reliability in multiphase, national cross‐sectional survey of the full roster of certified nurse‐midwives and certified midwives practicing in the United States. To test structural validity and reliability testing, 2 subsamples of 330 participants were randomly extracted from the sample of 2887 for exploratory and confirmatory factor analyses and internal consistency determination. Convergent validity was tested in the remaining sample of 1673 respondents. Results: Exploratory factor analysis revealed 2 5‐subscale structures consistent with the loading values and theoretical structure. Confirmatory factor analysis revealed a mediocre fit of the models identified in the exploratory analysis. Consequently, items were systematically reviewed for redundancy, skew, and generalizability and 24 items were removed from the scale. The resulting structure is a 10‐item scale comprising 2 subscales: Practice Leadership and Participation and Support for the Midwifery Model of Care. The revised Midwifery Practice Climate Scale was a good fit with the data demonstrating adequate construct validity (χ 2 = 60.397, df = 34, P < 0.001; comparative fit index, 0.987; root mean square of approximation, 0.049) and internal consistency (α = 0.89‐0.84). Discussion: These findings indicate that the Midwifery Practice Climate Scale accurately and reliably measures the midwives' perceptions of their practice environment. The next steps include determining the scale's sensitivity to change and assessing the relationship with maternal health outcomes.